A complex system of learning to drive: The instructor's perspective. (April 2021) - Watson-Brown, Natalie; Mills, Laura; Senserrick, Teresa; Freeman, James; Davey, Jeremy; Scott-Parker, Bridie
Highlights: Instructors provided unique insights that could enhance graduated driver licensing. The purpose of graduated driver licensing is not well understood by key stakeholders. Instructors perceived accreditation training insufficient to develop safe young drivers. Instructors need skills that target learner drivers' risky behaviours. Parental supervision identified by instructors as critical to effective learner driver training. Abstract: Driving instructors offer important support to the development of young motorists' safe and competent driving practices. Research has generally neglected to consider instructors' perspectives when exploring opportunities to improve novice driver road safety. In the application of systems thinking to road safety it is evident that instructors can play a central role in stakeholder interactions. Importantly, to further improve the successes of graduated driver licensing, instructors are integral in their interactions with Learners and their supervising parents. The current study aimed to understand 13 driving instructors' perspectives regarding experiences of Learner driver training including interactions with Learners' parents. Semi-structured interviews were conducted, and inductive thematic analysis employed, identifying 10 themes: 100 h of supervised driving, pressure to teach to pass the test, perceived shortcomings in instructor training, inconsistent messaging, parents' learning disengagement, parents as 'trainers' or 'supervisors', expectations of professional instruction, Learners' risky attitudes, bad habits, and a message for parents . A consistent message was found in instructors' narratives regarding a better understanding of the underlying rationale of graduated driver licensing (GDL) requirements (e.g., the purpose of 100 h of supervised driving), critical given the value of parents and professional instructors working collaboratively to enhance young drivers' safe driving skills. Practical implications for the driver trainer industry include demand for standardisation of both qualifications and practice within the driving instructor cohort. And for parents, ensuring appropriate knowledge is provided to enable an understanding of the essential components of GDL and the reciprocal roles and benefits offered by professional instructors.